The problem of dissolution doline definition - Stepišnik, Uroš (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2015)
Dolines are regularly referred as diagnostic karst landforms, as their formation is usually attributed to chemical weathering or dissolution, which is the most typical karst process. In this paper, we re-evaluate the formation of the two most typical dissolution dolines, provided by Cvijić. Within this study, we stated that both cases, which constitute the foundations of interpretation of dissolution dolines formation, are actually not caused by dissolution of the surface. The purpose of the article is to provide a doubt about the understanding of formation of the most common karst landform.
Keywords: geomorfologija; geomorphology; karst; korozija; kras (geologija); krasoslovje; kraški pojavi; Slovenia; Slovenija; vrtače